Buen Vivir, a decolonial approach to development - Morales Pachón, Andrés; Calvo, Sara (Social innovation in Latin America: maintaining and restoring social and natural capital, 2021)
This chapter presents the Buen Vivir (BV) as a decolonial approach to development. BV emerges as a consequence of the failures of development and is built upon the objective to identify ‘alternatives to development’, rather than ‘development alternatives’, as a concrete possibility through ecological and cultural transitions. Development is a concept that is still under discussion and subjected to the myriad and manifold definitions of it. The reality in the region, suggested by the existing literature, is that there is a significant and substantial work about the possibility of a new development paradigm, and BV is an example of it. BV is inspired and influenced by the Andean ‘cosmovision’ of indigenous peoples in Latin America. Community or Ayllu is an essential aspect of indigenous people in the Andes and the exercise of community cohesion is inherited by their ancestors.
Keywords: decolonial approach; development; Scopus(2); WOS(2)